2004
DOI: 10.1159/000077452
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Effects on Markers of Autonomic Nervous System Function in the Piglet: Implications for SIDS

Abstract: The hypothesis was tested in 30 newborn piglets that the effects of a low dose of endotoxin (1 µg i.v. bolus; Salmonella abortus equi) would impair autonomic nervous system function. Two tests of autonomic function were performed following external warming (pre-endotoxin) and during endotoxin-generated thermogenesis: (1) analysis of heart rate variability in the time and frequency domains and (2) baroreflex sensitivity measured following intravenous injection of the vasoactive drugs nitroprusside and phenyleph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Heart rate variability, referring to the changes in beat to beat heart rate measured over a period of a RR-interval recording (tachogram) [8,9], has been proven as a valid method to assess stress in humans [8] and animals [10], including horses [5,6,[11][12][13][14], pigs [15,16], sheep and goats [17][18][19], cattle [20,21], poultry [22], and dogs [23,24]. Studies in humans showed that standardization of methodology is important to assure inter-and intra-study repeatability of HRV measurements [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability, referring to the changes in beat to beat heart rate measured over a period of a RR-interval recording (tachogram) [8,9], has been proven as a valid method to assess stress in humans [8] and animals [10], including horses [5,6,[11][12][13][14], pigs [15,16], sheep and goats [17][18][19], cattle [20,21], poultry [22], and dogs [23,24]. Studies in humans showed that standardization of methodology is important to assure inter-and intra-study repeatability of HRV measurements [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that the balance of autonomic tone was altered and autonomic responsiveness reduced in piglets during the thermogenic phase of a fever [15] . The impairment to autonomic function implied by these fi ndings may be refl ected in dysfunction of airway mechanoreceptors [16,17] .…”
Section: Effect Of Endotoxin On Respiratory Responsivenessmentioning
confidence: 83%
“…raised body temperature with heat-releasing mechanisms operating), has not been explored. Findings from our laboratory on neonatal piglets have shown that experimentally induced endotoxin-generated thermogenesis is associated with a reduction in heart rate variability and barorefl ex sensitivity [15] . The impairment to autonomic function implied by these fi ndings may be refl ected in dysfunction of airway mechanoreceptors [16,17] , which are important for the initiation of protective responses during upper airway obstruction [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it also indicates affected control of breathing that can lead to respiratory instability and fatal apnea, and contribute to the pathophysiology of sudden infant death syndrome (SIDS). Multifactorial etiology of SIDS include bacterial toxemia, increase in core temperature and autonomic dysfunction (Gilbert et al, 1992;Stoltenberg et al, 1994;Voss et al, 2004) and thus decreased power of Hering-Breuer reflex in fever probably reflects altered autonomic function mediated via vagal mechanisms in control of breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, increase in BT modifies breathing pattern and contributes to respiratory instability in thermal stress (Voss et al, 2004). The effects of changing vagal neural mechanisms in endotoxin-induced fever are unknown and the pathways mediating thermoregulatory influences on respiratory activity remain to be investigated (Morrison and Nakamura, 2011).…”
Section: Introductionmentioning
confidence: 99%